Evaluation of infections in patients with kidney and liver transplantation - Doğan Kaya, Sibel; Evik, Güliz; Deniz, Münire; Uygun Kızmaz, Yeşim (The European Research Journal, 2023)
Objectives: Infection is a frequent complication of organ transplantation and is associated with significant morbidity and mortality. Methods: Patients who had liver and kidney transplants between 2011 and 2022, who were hospitalized in our hospital, and who were consulted for infectious diseases were retrospectively analyzed from hospital records. Results: Of the patients included in the study, 9 (28%) were female, 23 (72%) were male, and the mean age was 33.7 ± 11.3 years. Patients had congestive heart failure (87.2%, n = 28, hypertension (43.7%, n = 14), and chronic obstructive pulmonary disease (21.8%, n = 7). Twenty (62.5%) kidney transplant recipients and 12 (37.5%) liver transplant recipients were seen within ten years. The most common infections were urinary tract infection in 8 ( 25%) patients and pneumonia in 11 (34.3%). The other infections were gastrointestinal infections such as diarrhoea, bloodstream infections and COVID-19 and Cytomegalovirus. Culture-isolated organisms in 20 (62.5%) of the 32 patients admitted with infections. The microbiological data were notable for some unusual and opportunistic pathogens, including one case of acute cytomegalovirus viremia. Severe sepsis had been seen in six (18.75%) out of 32 patients with documented infections. Conclusions: Infection prevention has become a cornerstone of modern transplantation medicine due to the significant incidence of post-transplant infectious complications resulting from improved immunosuppressive therapies and surgical procedures.